Trends and factors associated with cesarean sections in Brazil and its States between 2001 and 2015 - Garabeli Cavalli Kluthcovsky, Ana Claudia; Christino da Silva Amari, Valeria; Ramos Esperidião, Cristine; Martins Ciriaco, Evelise; Barauce Freitas, Nicolle; Trevisan Vernizi, Bruna (O Mundo da Saúde, 2019)
This study aimed to analyze the trends and socioeconomic factors associated with cesarean sections that occurred in Brazil and its states from 2001 to 2015. As hypotheses, it was suspected that there would be an increasing trend in the proportion of cesarean sections and an association with a higher socioeconomic status of women. This was an ecological and cross-sectional study with data collected from the Live Birth Information System and the National Household Sample Survey. The proportions and trends of cesarean sections in relation to normal births were calculated for three years. The temporal trend was calculated by simple linear regression models and the correlation between the proportion of cesarean sections and socioeconomic factors were by the Spearman correlation coefficient, with a significance level of 5%. From the 2010-2012 triennium, all states had caesarean sections greater than 30%. The largest proportions of cesarean sections were observed in the last three years analyzed from 2013 to 2015; the lowest being 34.9% and the highest 66.8%. Between 2007 and 2015 in all states of the Midwest, Southeast and Southern Regions the amount exceeded 50%. All states showed a significant tendency for cesarean sections to increase over time. There was a positive and significant correlation between the number of cesarean sections and per capita income, households with garbage collection and the Human Development Index, and there was a negative correlation for the percentage of the population with incomes below half one minimum wage. The high rate of cesarean sections in Brazil indicates the need for specific interventions through public policies aimed at maternal and child health.